UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS I SDN 1 PADAAN DALAM MELAKUKAN PENJUMLAHAN DAN PENGURANGAN MELALUI PENDEKATAN KETERAMPILAN PROSES DENGAN MEDIA DADU - Siswati, Siswati (Universitas Negeri Semarang, 2016)
The problems of this research are classical learning without relevant media and the students with weak of numeral concept understanding and calculation. This research is Class Action Research (CAR), consist of two cycles with 23 students as the research subject. The action on the first cycle is using dice with simple circle symbolic. The action on the second cycle is using dice with colored circle symbolic. The results of this research are 1) the using of dice as the media make the learning interesting, concrete and effective, 2) the renewal of dice with colored circle symbolic abridge the students to calculate on story questions, 3) the using of dice as the media increase the students’ calculation.